Cold-active lipases and esterases: a review on recombinant overexpression and other essential issues - Matinja, Adamu Idris; Ahmad Kamarudin, Nor Hafizah; Thean, Adam Chor Leow; Oslan, Siti Nurbaya; Mohamad Ali, Mohd Shukuri (MDPI, 2022)
Cold environments characterised by diverse temperatures close to or below the water freezing point dominate about 80% of the Earth’s biosphere. One of the survival strategies adopted by microorganisms living in cold environments is their expression of cold-active enzymes that enable them to perform an efficient metabolic flux at low temperatures necessary to thrive and reproduce under those constraints. Cold-active enzymes are ideal biocatalysts that can reduce the need for heating procedures and improve industrial processes’ quality, sustainability, and cost-effectiveness. Despite their wide applications, their industrial usage is still limited, and the major contributing factor is the lack of complete understanding of their structure and cold adaptation mechanisms. The current review looked at the recombinant overexpression, purification, and recent mechanism of cold adaptation, various approaches for purification, and three-dimensional (3D) crystal structure elucidation of cold-active lipases and esterase.